Risk Analysis and Calculation of Insurance Premiums on Coffee Export Activities in North Sumatera Province - Ayu, Sri Fajar; Sunny , Rainal; Rahmanta (Talenta Publisher, 2020)
Coffee export activities in North Sumatera can be carried out using a variety of transaction systems. However, any transaction system has risks that may occur at any time. Risk management must be applied in coffee export activities. One common method used to manage risk is to use insurance services. This study aims to identify the type of transaction system that used by coffee exporters in North Sumatera Province, then analyze the risks that can occur in coffee export activities in this province and analyze the amount of insurance premiums on coffee export activities there. The location of the study was intentionally determined, namely in the North Sumatera Province. The research sample was 30 active exporters registered with the Indonesian Coffee Exporters Association of the North Sumatera Regional Board, determined by census. Primary data collected using a questionnaire and secondary data obtained from documentation. Transaction system identified using descriptive methods, while risk analysis is by calculating the risk score value. As for calculating the amount of insurance premiums carried out using Black-Scholes. The results found that there were three transaction systems that were used by research respondents in exporting coffee, namely letters of credit, advance payments and open accounts. Open Account is used by all respondents. While the export risk which is a priority risk in this research is at the risk of production. The average value of insurance premiums obtained using the Black-Scholes method is 7.82 percent of the total coverage.